Hand-assisted laparoscopic nephrectomy in a donor with triple renal vessels - Branco, Anibal Wood (2005)
Objective: Donor availability is an important limiting factor in renal transplant programs; consequently, it is important to be able to use every vital organ independent of the vascular anatomy. Method: It is reported a successful case-story of hand-assisted laparoscopic nephrectomy in a 69-year-old related donor with triple renal vessels. The estimated blood loss was of 100 mL, the operative time was of 80 minutes and the warm ischemia time was of 3.0 minutes. The transplant was performed in the left iliac fossa. The donor experienced an excellent recovery, and she was discharged in the second postoperative day. The recipient was discharged home in the8th postoperative day, and her creatinine level was of 1.3mg%. Discussion and Conclusion: It was demonstrated the feasibility of hand-assisted laparoscopic nephrectomy in a patient with triple renal vessels, and we also share the opinion that in experienced hands, all procedures can be done by laparoscopy with no additional risk to the donor and/or the recipient.